Optimalisasi Pertumbuhan dan Hasil Tanaman Kacang Panjang (Vigna sinensis L.) dengan Pemanfaatan Mikroorganisme Lokal Rebung Bambu dan Pupuk NPK Mutiara - Kholilullah Kholilullah; Silvia Fitri Mei Arini (Program Studi Agroteknologi, 2026)
This study aimed to optimize the growth and yield of yardlong bean (Vigna sinensis L.) through the application of local microorganisms (MOL) derived from bamboo shoots and the use of NPK Mutiara fertilizer. The research was conducted in Sidomukti Village, Mayang Subdistrict, Jember Regency, East Java, at an altitude of 297 meters above sea level, from September to December 2024. A factorial randomized complete block design (RCBD) was employed with three replications and two treatment factors. The first factor was the concentration of bamboo shoot MOL (M), consisting of four levels: M0 = control, M1 = 10 mL/L per plant, M2 = 20 mL/L per plant, and M3 = 30 mL/L per plant. The second factor was the dosage of NPK Mutiara fertilizer (P), consisting of three levels: P1 = 10 g/plant, P2 = 20 g/plant, and P3 = 30 g/plant. The observed parameters included plant height, number of leaves per plant, number of pods per plant, pod length per plant, fresh pod weight per plant, and root weight per plant. Collected data were analyzed using analysis of variance (ANOVA), and significant differences were further tested using Duncan’s Multiple Range Test at a 5% significance level with Microsoft Excel. The results showed that bamboo shoot MOL concentrations had no significant effect on any of the observed parameters. However, the application of 20 g/plant NPK Mutiara fertilizer (P2) significantly affected plant height. Furthermore, the interaction between 30 mL/L bamboo shoot MOL and 30 g/plant NPK Mutiara (M3P3) significantly influenced the number of pods per plant.